Pengaruh Kemiskinan Terhadap Indeks Pembangunan Manusia (IPM) Dalam Perspektif Ekonomi Islam Di Kabupaten Tulungagung Tahun 2013 – 2022 - Alfiandika, Ahsan Maulana Nur; Pramudita, Ajeng Ayu; Furoidah, Fatia Afni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
ABSTRACT. This study aims to analyze the impact of poverty and economic growth on the Human Development Index (HDI) in Tulungagung Regency between 2013 and 2022. Data related to poverty levels and HDI were collected over this ten-year period, broken down into forty quarters to obtain a more detailed picture of their interrelationship and impact on human development in the region. The data analysis conducted aims to display the extent of the role of poverty and economic growth in changing HDI in Tulungagung Regency, as a basis for formulating the influence of these two factors on the human development index. The analysis method used includes simple linear regression, where the analysis tools used are IBM SPSS Statistic 27 and Eviews-13 statistical software. The results show that partially, poverty has a significant impact on the human development index. A strong relationship between poverty level and HDI is illustrated, where the higher the poverty level, the lower the HDI. Meanwhile, HDI in the Islamic context is defined based on the concept of maqashid sharia, which includes the protection of religion, soul, mind, offspring, and property. Keywords: Influence; Poverty; Human Development; Economic Growth; Islamic Economics